A homozygous mutation in a consanguineous family consolidates the role of ALDH1A3 in autosomal recessive microphthalmia. (25th October 2013) - Roos, L.; Fang, M.; Dali, C.; Jensen, H.; Christoffersen, N.; Wu, B.; Zhang, J.; Xu, R.; Harris, P.; Xu, X.; Grønskov, K.; Tümer, Z.
<x xml:space="preserve">Abstract</x> Anomalies of eye development can lead to the rare eye malformations microphthalmia and anophthalmia (small or absent ocular globes), which are genetically very heterogeneous. Several genes have been associated with microphthalmia and anophthalmia, and exome sequencing has contributed to the identification of new genes. Very recently, homozygous variations within ALDH1A3 have been associated with autosomal recessive microphthalmia with or without cysts or coloboma, and with variable subphenotypes of developmental delay/autism spectrum disorder in eight families. In a consanguineous family where three of the five siblings were affected with microphthalmia/coloboma, we identified a novel homozygous missense mutation in ALDH1A3 using exome sequencing. Of the three affected siblings, one had intellectual disability and one had intellectual disability and autism, while the last one presented with normal development. This study contributes further to the description of the clinical spectrum associated with ALDH1A3 mutations, and illustrates the interfamilial clinical variation observed in individuals with ALDH1A3 mutations.